Elucidating the molecular mechanism of drug binding and translocation by the multidrug transporter ABCG2 - Kapoor, Parth (2020)
Many drug resistant tumours express one or more of the three main drug efflux transporters, P-glycoprotein (ABCB1), multidrug resistance protein 1 (MRP1; ABCC1) and breast cancer resistance protein (ABCG2). These transporters facilitate the export of diverse range of structurally unrelated compounds from the cell. ABCG2, is widely distributed in tissues, contributes towards normal physiology and pharmacokinetic profiles of many exogenous drugs. It is this promiscuous drug binding and transport that makes it an appealing target for research. The aim of this project is to better understand the molecular mechanism of multidrug binding and transport by ABCG2. Here we focus on two specific regions of the protein: transmembrane helix 3 (TM3) and the NBD: NBD (nucleotide binding domain) interface to elucidate their role in the function of ABCG2 transporter.